Shallot Marketing Structure, Efficiency, and Challenges in an Island Region (Structure, Conduct, and Performance Analysis in Tomia Timur, Indonesia) - Ramli Ramli; Wardana Rifani; Mustari Mustari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study analyzes the structure, conduct, and performance (SCP) of shallot marketing in Tomia Timur District, Wakatobi Regency, Indonesia, an isolated island region with limited logistics. Using a descriptive approach, the research involved 30 shallot farmers and nine traders as respondents, selected through purposive, accidental, and snowball sampling methods. The results show an oligopsonistic market structure with high concentration at the trader level and competitive behavior among farmers. Traders dominated price-setting, while farmers acted as price takers. The marketing margin varied significantly across institutions, and the farmer's share was only 38.94%, below the fair threshold. The primary marketing obstacles were capital constraints and unfavorable pricing conditions. These findings highlight the need for market interventions in archipelagic agricultural zones to improve farmers' bargaining positions and marketing efficiency.